Stimulation of DC-CIK with PADI4 Protein Can Significantly Elevate the Therapeutic Efficiency in Esophageal Cancer. (3rd March 2019) - Liu, Chunyan; Zheng, Yingying; Tang, Junyi; Wang, Dawei; Ma, Zhenshen; Li, Shutong; Chang, Xiaotian
Abstract : Background . PADI4 has extensive expression in many tumors. This study applied PADI4 as a tumor marker to stimulate DC- (dendritic cell-) CIK (cytokine-induced killer), an immunotherapy approach. Methods . A PADI4 expression plasmid was transfected into EC-originating ECA-109 cells. PADI4 gene was also inserted into a prokaryotic expression vector to produce recombinant protein. Lysate from PADI4-overexpressing cells or the purified recombinant PADI4 protein was used to load DCs, and the cells were then coincubated with CIK cells. DC and CIK cell phenotypes were determined using flow cytometry. The proliferation and viability of CIK cells were analyzed using trypan blue staining. The cytotoxic effect of DC-CIK cells on cultured ECA-109 cells was determined using CCK8 assays. Tumor-bearing mice were prepared by injection of ECA-109 cells. DC-CIK cells stimulated with lysate from PADI4-overexpressing cells or the PADI4 recombinant protein were injected into the tumor-bearing mice. The tumor growth was measured with magnetic resonance imaging (MRI). Results . Following incubation with lysate from PADI4-overexpressing cells, the ratio of CD40 + DCs increased by 17.5%. Induction of CIK cells with PADI4-stimulated DCs elevated the cell proliferation by 53.2% and the ability of CIK cells to kill ECA-109 cells by 12.1%. DC-CIK cells stimulated with lysate from PADI4-overexpressing cells suppressed tumor volume by 18.6% in the tumor-bearing mice. The recombinant PADI4 protein showed a similar effect on CIK cell proliferation and cytotoxicity as that of the lysate from PADI4-overexpressing cells. Furthermore, the recombinant protein elevated the ratio of CD40 + DCs by 111.8%, CD80 + DCs by 6.3%, CD83 + DCs by 30.8%, and CD86 + DCs by 7.8%. Induction of CIK cells with rPADI4-stimulated DCs elevated the cell proliferation by 50.3% and the ability of CIK cells to kill ECA-109 cells by 14.7% and suppressed tumor volume by 35.1% in the animal model. Conclusion . This study demonstrates that stimulation of DC-CIK cells with PADI4 significantly suppressed tumor growth in tumor-bearing mice by promoting DC maturation, CIK cell proliferation, and cytotoxicity. PADI4 may be a potential tumor marker that could be used to improve the therapeutic efficiency of DC-CIK cells.